Man trouble - Rafelson, Bob 1933-; Gilbert, Bruce 1946-; Eastman, Carole 1934-2004; American Filmworks/Budding Grove production (Beverly Hills, California 20th Century Fox Home Entertainment, 1992)
In this wild, romantic comedy with a decidedly offbeat sense of humor, Harry, a wise cracking con-man who owns a guard dog agency. When Joan, an opera singer, seeks his aid after her house is broken into, Harry inadvertently makes them the target of hit men - and puts them at eh mercy of Harry's out-of-control canines.
Production designer, Mel Bourne ; Edited by William Steinkamp ; Executive producer, Victorio Cecchi Gori ; Co-executive producer, Gianni-Nunnart.
Jack Nicholson, Ellen Barkin, Harry Dean Stanton, Beverly D'Angelo, Michael McKean, Saul Rubinek, Veronica Cartwright.
PG-13
DVD (Region 1, NTSC) ; Anamorphic widescreen (1.85:1) ; Dolby Digital
In English with English and Spanish subtitles.
Keywords: Comedy films